Precursor ion scan driven fast untargeted screening and semi-determination of caffeoylquinic acid derivatives in Cynara scolymus L. (1st January 2015) - Shen, Qing; Lu, Yanbin; Dai, Zhiyuan; Cheung, Hon-Yeung
Highlights: CADs were untargeted screened based on PIS scan from artichoke. Ten caffeoylquinic acid derivatives were detected based on PIS of m / z 191. The potential of precursor ion scan method for semi-determination was evaluated. Abstract: A precursor ion scan (PIS) technique based strategy was developed for rapid screening and semi-determination of caffeoylquinic acid derivatives (CADs) in artichoke ( Cynara scolymus L.) using ultra-performance liquid chromatography (UPLC) coupled with tandem mass spectrometry. 1, 5-Dicaffeoylquinic acid and 5-caffeoylquinic acid were used for studying the fragmentation behaviour of two classes of CADs, setting m / z 191 as a diagnostic moiety. When it was applied to artichoke sample, ten CADs were detected and elucidated in a single PIS run. Furthermore, method validation was implemented including: specificity (no interference), linearity (⩾0.9993), limit of detection (LOD < 0.12 ng mL −1 ) and limit of quantification (LOQ < 0.25 ng mL −1 ), precision (RSD ⩽ 3.6), recovery (91.4–95.9%) and stability (at least 12 h). This approach was proven to be a powerful, selective and sensitive tool for rapid screening and semi-determination of untargeted components in natural products.